Influência da composição corporal na capacidade funcional e efeitos do treinamento de alta e baixa intensidade na musculatura inspiratória em indivíduos com DPOC grave e desnutridos - Ruas, Gualberto (2013)
The thesis consisted of two studies described below. The study I, entitled: "The influence of body composition measured by dual-energy absorptiometry functional capacity in patients with chronic obstructive pulmonary disease", aimed to analyze the influence of body composition assessed by dual-energy x-ray absorptiometry on functional capacity in patients with chronic obstructive pulmonary disease (COPD). We Eleven male patients with COPD (COPDG), 7 presenting moderate obstruction and 4 severe, and 11 sedentary male subjects (CG) were evaluated by dual-energy x-ray absorptiometry to assess their body composition, all subjects have also performed the 6 minute walk test (6MWT) and step test (6MST) to assess their functional capacity. No significant differences were found between groups for anthropometric data such as age, weight, height and body mass index (BMI). However, the COPDG presented forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC ratio, maximal voluntary ventilation (MVV),walked distance (WD) and number of steps (NS) significantly lower than the CG (p<0,05; Student s t test). The body bone mass (BBM), BBM%, Lean Mass (LM), LM%, and right lower limb (RLL) and left lower limb (LLL) were significantly lower in the COPDG when compared with the CG, presenting statistically significant positive correlations with 6MWT on WD and 6MST on NS (p<0,05, Pearson s test). We conclude that body composition is an important prognostic factor for patients with COPD, which reinforces the importance of assessing body composition by dual-energy absorptiometry since it has demonstrated with satisfactory accuracy in clinical practice. Moreover, it is a parameter useful evaluation and reassessment in pulmonary rehabilitation programs. Following the II study entitled: "Effects of training of high and low intensity in musculature inspiratory in individuals with severe COPD and malnourished," which aimed to verify and analyze the effects of training in high and low intensity inspiratory muscles in patients with severe COPD and malnourished. We evaluated 32 men with severe COPD and malnourished, divided into two groups (G1 and G2). Assessments of the degree of dyspnea, pulmonary function test, MIP, WD, SGRQ and DM were performed at pre-training and after 12 weeks of training. We found that G1 got significant increase in MVV, MIP, WD and DM, and significant decreases in the percentages MRCm and SGRQ at 12 weeks of training, which remained after 12 weeks without training. Group 2 showed the same behavior when compared with the G1 at 12 weeks of training, but values returned to the initial MVV, MRCm, DM and MIP and WD had values below the baseline, and the percentage increased significantly SGRQ after 12 weeks without training. In the intergroup analysis (12-12 weeks) G1 showed higher values in MVV, MIP, WD and DM values and smaller percentages in the SGRQ compared with G2. Comparing the 24-24 weeks, G2 showed lower values in MVV, MIP, WD and DM and significant increases in the percentages MRCm and SGRQ compared with G1. The TMI high and low intensity promoted benefits to individuals with severe COPD and malnourished, which were maintained after 12 weeks of high intensity training.